2016
DOI: 10.1002/2015jb012534
|View full text |Cite
|
Sign up to set email alerts
|

Major disruption of D″ beneath Alaska

Abstract: D″ represents one of the most dramatic thermal and compositional layers within our planet. In particular, global tomographic models display relatively fast patches at the base of the mantle along the circum‐Pacific which are generally attributed to slab debris. Such distinct patches interact with the bridgmanite (Br) to post‐bridgmanite (PBr) phase boundary to generate particularly strong heterogeneity at their edges. Most seismic observations for the D″ come from the lower mantle S wave triplication (Scd). He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 91 publications
4
24
0
Order By: Relevance
“…These velocity jumps range from 0.48% (in mod7) to 2.52% (in mod11). The strength of these velocity discontinuities is similar to that reported for downwelling regions (e.g., Helmberger et al, 2005; Sun et al, 2016; Yao et al, 2015; Young & Lay, 1987a, 1987b). …”
Section: Apparent Splitting For a Deep Earthquake Sourcesupporting
confidence: 87%
“…These velocity jumps range from 0.48% (in mod7) to 2.52% (in mod11). The strength of these velocity discontinuities is similar to that reported for downwelling regions (e.g., Helmberger et al, 2005; Sun et al, 2016; Yao et al, 2015; Young & Lay, 1987a, 1987b). …”
Section: Apparent Splitting For a Deep Earthquake Sourcesupporting
confidence: 87%
“…Recent waveform forward modeling studies (He et al 2014;Sun et al 2016) estimated depths of the D′′ discontinuity of ∼200 and ∼250 km above the CMB beneath Kamchatka and the Northern Pacific, respectively, which are consistent with the depth of the significant high-velocity anomalies between 200 and 300 km above the CMB in our model (Figs. 2, 3).…”
Section: Discussionsupporting
confidence: 72%
“…He et al (2014) suggested an 850-kmthick low-velocity anomaly surrounded by a 210-km-thick high-velocity anomaly in D′′ beneath Kamchatka on the basis of forward modeling of seismic waveforms. Sun et al (2016) studied the lowermost mantle beneath Alaska using waveforms recorded at recently deployed USArray stations. They divided the study area into three subregions with lateral scales of ∼15 • (western, middle, and eastern parts).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These strong lateral heterogeneities are much larger than those calculated from global tomographic models and imply significantly complex structures at the CMB that have long been known to exist [see Garnero (2000); Lay and Garnero (2011) for a review], even on the small-scale level (Ma et al 2016;Sun et al 2016). The explanations for these heterogeneities, however, are still inconclusive.…”
Section: Ulvzs At the Cmbmentioning
confidence: 98%